Meningkatkan Minat Berwirausaha Generasi Z Melalui Literasi Digital di Era Teknologi - Astri Rumondang Banjarnahor; Ovi Hamidah Sari (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This study examines the impact of digital literacy on the interest and readiness of Generation Z to engage in entrepreneurship in the era of technological transformation. Findings from a digital entrepreneurship socialization program revealed a significant increase in Generation Z's understanding and motivation to initiate technology-based businesses after participating in training and discussions. One major challenge identified was the lack of comprehensive digital literacy, including skills in data analysis, e-commerce platform management, and strategic digital marketing. Evaluation through pre- and post-tests showed that digital literacy effectively builds participants' confidence in utilizing technology to plan and manage businesses. Additionally, the collaboration between educational institutions, the government, and the private sector is essential in creating a sustainable ecosystem of learning and guidance to support the growth of digital entrepreneurship among Generation Z. With adequate digital skills and understanding, Generation Z holds a greater potential for innovation, competitiveness, and contribution to the digital economy.